Survey on user authentication protocol in wireless sensor network - Wei-dong FANG; Wu-xiong ZHANG; Lian-hai SHAN; Wei HE; Wei CHEN (网络与信息安全学报)
In wireless sensor network (WSN), the user authentication technology is an effective approach, which can guarantee the user's validity, avoid WSN's information disclosure. Meanwhile, the users also need to verify the WSN's validity, avoid obtaining incorrect or false information. However, since the sensor nodes have limited energy, communications and computing capacity, and they are usually deployed in hostile or unattended environment, the traditional user authentication protocol (UAP) is not entirely suitable for WSN. The security attacks were introduced for the UAP in WSN, its secure requirements and the theoretical foundation were given, and then the UAP's design processes were summarized. For the analysis of its security, the attack model was described, and the automated vali-dation of internet Security protocols and applications (AVISPA) and the high level protocols specification language (HLPSL) were overviewed in detail. Then, the current UAPs were reviewed in WSN, the future research directions were proposed. These researches will contribute to the design, analysis and optimization for the UAP in WSN.